Mesenchymal stem cells and pulmonary fibrosis: a bibliometric and visualization analysis of literature published between 2002 and 2021 - Yang, Yanli; Chen, Yu; Liu, Yang; Ning, Zongdi; Zhang, Zhaoliang; Zhang, Yan; Xu, Ke; Zhang, Liyun (Frontiers in Pharmacology, 2023)
Pulmonary fibrosis (PF) is a severe disease that can lead to respiratory failure and even death. However, currently there is no effective treatment available for patients with PF. Mesenchymal stem cells (MSCs) have been recently shown to have therapeutic potential for PF. We analyzed the literature focused of MSCs and PF to provide a comprehensive understanding of the relationship between MSCs and PF. We searched the Web of Science Core Collection database for literature involving MSCs and PF from 2002 to 2021. We identified and analyzed a total of 1,457 using CiteSpace and VOSviewer. Our analysis revealed the following findings: 1) The number of publications focused on MSCs and PF research increased during the study period; 2) Among the 54 countries/regions of author affiliations, most articles were published in the United States of America, and the University of Michigan (n=64, 2.8%) had the largest number of publications; 3) Rojas Mauricio published the most articles and PLOS ONE had the most related studies; 4) Keywords, such as idiopathic pulmonary fibrosis, MSCs, and systemic sclerosis, were listed more than 100 times, representing a research trend. Other common keywords included inflammation, myofibroblasts, fibroblasts, aging, telomerase or telomere, and extracellular matrix. Our analysis provides new insights into the current status and research trends in the field of MSCs and PF during the past two decades.